2014
DOI: 10.1161/hypertensionaha.113.03206
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk With and Without Antihypertensive Drug Treatment in the Japanese General Population

Abstract: Abstract-To evaluate the cardiovascular mortality risk in association with blood pressure level among people with and without antihypertensive treatment, we performed the participant-level meta-analysis that included 39 705 Japanese from 6 cohorts (58.4% women; mean age, 60.1 years; 20.4% treated). Multivariable-adjusted Cox models were used to analyze the risk of cardiovascular mortality and its subtypes among 6 blood pressure levels according to recent guidelines, optimal to Grade 3 hypertension, and the usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Furthermore, we estimated the absolute disease risks for incident CVD associated with different levels of BP in the community and demonstrated that treated hypertensives had a greater risk of incident CVD compared with untreated participants with similar BP. These observations are in line with the results from population‐based analyses from Japan and Sweden reporting greater risks of cardiovascular mortality and stroke in treated versus untreated persons 9, 10, 11. Finally, we report that the increased hazard for CVD is attenuated by ≈3% to 20% on adjustment for the greater subclinical disease burden in treated hypertensives, consistent with the concept that part of the increased CVD risk is related to the greater subclinical disease burden.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we estimated the absolute disease risks for incident CVD associated with different levels of BP in the community and demonstrated that treated hypertensives had a greater risk of incident CVD compared with untreated participants with similar BP. These observations are in line with the results from population‐based analyses from Japan and Sweden reporting greater risks of cardiovascular mortality and stroke in treated versus untreated persons 9, 10, 11. Finally, we report that the increased hazard for CVD is attenuated by ≈3% to 20% on adjustment for the greater subclinical disease burden in treated hypertensives, consistent with the concept that part of the increased CVD risk is related to the greater subclinical disease burden.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have used similar designs in a variety of populations, including normotensive subjects, to assess cardiovascular risk related to BP over a wide BP range. [22][23][24] Each study has unique features pertaining to special aspects of their population and BP data.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale, study design, and methods of the EPOCH-JAPAN study have been described elsewhere 9, 10, 11, 12, 13, 14, 15. In brief, cohort studies were eligible for inclusion in this analysis if they met the following criteria: (1) collection of health examination measures, (2) at least 10 years of follow-up, and (3) greater than 1000 participants.…”
Section: Methodsmentioning
confidence: 99%